Brazil : Financial Sector Assessment Program-Technical Note on Stress Testing and Systemic Risk Analysis. (IMF Staff Country Reports; Country Report ;, 2018)
The financial system has been resilient through the severe recession. Banks and investment funds dominate Brazil's financial system landscape. The banking sector has continued to be well-capitalized, profitable, and liquid. Profitability has been supported by prudent lending standards, high interest margins and robust fee income, despite record loan losses. Outstanding nonperforming loans have increased marginally during the recession largely because banks have actively written off bad loans. The investment fund industry has also been solid, enjoying a steady growth of assets under management without experiencing net outflows, in aggregate, during the recession. Market-based indicators point to relatively low levels of systemic risk in 2017. However, the outlook for the nonbank sector will become more challenging in the environment of lower interest rates, as lower returns will affect investment income and a search for yield may increase risk-taking.